La gramática castellana de Caramuel (1663) - Martínez Gavilán, María Dolores (Estudios humanísticos. Filología, 1990)
Juan Caramuel y Lobkowitz (born Madrid, 1606-died Vigevano, 1682) was the author of a philosophical mediaeval style grammar in which many of the postulares of the speculative grammar Grammatica audax (1654) are resucitated. This must connected with his position in the terrain of philosophy and theology wich was clearly a scolastic one. Indeed, he has been considered as one of the forerunnes of the Grammaire générale et raisonnée of Port-Royal His contributions to the field of general or universal grammar ha ve been put finto relief by various scholars (V. Salmon, H E. Brekle, G. A. Padley, E Delgado) whose points of view are reviewed here.The objetive of what follows is two-fold a) to analyze his contribution to the fíeld of specific grammar, with especial reference to Spanish grammar, and b) to disco ver to what extent the anlytic guidelines employed in his general grammar are present there.We will be dealing with the brief Castillian grammar which is included in his poetic treatise Primos Calamos (Rome, 1663). In this study a symbiosis of the topics developed by classic Greek-latin and later assimilated by the grammars of common or vulgar languages can be observed, together with some of the beginnings of the speculative mediaeval grammar, which the author had applied previously in his philosophic grammar.